Credit risk measurement : new approaches to value at risk and other paradigms - Saunders, Anthony; Allen, Linda (New York : John Wiley, 2002)
This book follows a ''building block'' approach. Chapter 1 provides the motivation for the recent growth of the new credit risk models. Chapter 2 briefly overviews traditional models of credit risk measurement. Chapter 3 through 8 examine the approaches of the new models to evaluating individual borrower(or counterparty) credit risk and to the valuation of individual loans.
Includes bibliographical references (p. 258-275) and index.
gau 30/04/14
Loans
Keywords: Bank management; Risk management; Credit; Bank loans